Improving the Pace of Criminal Case Processing in State Trial Courts - Ostrom, Brian J. (Criminal justice policy review, 2018)
Delay in the processing of criminal cases has long been viewed as a serious national problem. Substantial differences exist among courts in the average time it takes to resolve both felony and misdemeanor cases, with past research producing inconclusive results on the causes of observed variation. In response, and with the support of the Arnold Foundation, the objective of this article is to highlight predictable variation in the timeliness of criminal case processing and how this knowledge supports court efforts to become more expeditious. Drawing on an extensive set of felony and misdemeanor cases resolved in seven Colorado courts, statistical analysis uncovers important patterns in the composition of criminal caseloads and clarifies how composition influences case duration. Moreover, similarities in the makeup of criminal caseloads show the utility of fundamental principles of criminal caseflow management and how courts benefit from being assessed comparatively against established performance benchmarks.